Down the hole - Slater, Scott (Animator); Ming, Adam (Clarion Books, an imprint of HarperCollins Publishers, 2023)
Anansi the Spider meets Jon Klassen in this wickedly witty debut. When a suspiciously polite fox attempts to coax his next meal out of a burrow, he is met with a clever rabbit who has been cooking up a surprise for this very moment! Careful readers may spot what is in store for fox before he does in this darkly funny cautionary tale that roots for the underbunny.
Keywords: Foxes -- Juvenile fiction; Rabbits -- Juvenile fiction; Picture books